PROFITABILITAS STRATEGI KONTRARIAN DI BURSA EFEK INDONESIA - Burhanudin Burhanudin; I Gede Mandra; Laila Wardani (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2021)
The efficient market hypothesis implies that no investor can get an abnormal return. This hypothesis has become a research topic that many researchers refer to. However, this hypothesis is strongly refuted after the discovery of several anomalies that are inconsistent with the efficient market hypothesis. One of them was found by De Bondt and Thaler (1985), that stock prices have a certain tendency, namely that stocks that perform well in one period will become stocks that perform poorly in the next period. Vice versa. This phenomenon is called overreaction or overreaction. These findings motivated further researchers to apply contrarian strategies to gain an advantage when there was an overreaction. This research is a study that is intended to obtain evidence of the ability of contrarian strategies in obtaining abnormal returns. This study aims to analyze the occurrence of overreaction on stocks on the Indonesia Stock Exchange and to analyze the advantages of implementing a contrarian strategy for investors. This research was conducted at companies listed on the Indonesia Stock Exchange. The companies selected were 100 companies with the most active transactions during 2019. From the results of data analysis, it can be concluded that there was a price reversal for the shares listed on the Indonesia Stock Exchange. This result is quite strong because it has been tested for up to 4 weeks. Despite the price reversal, the contrarian strategy was not able to generate significant returns for investors.Keywords :contrarian strategy, abnormal return, overreaction